Transition layer sizing material for green and environment-friendly tire and production process of transition layer sizing material

By introducing carboxyl functional groups and forming an ionic crosslinking network on the surface of recycled carbon black, and combining it with bio-based adhesive resin to form a covalent crosslinking network with rubber, the problems of weak interfacial bonding and poor dispersibility of tire transition layer rubber under high stress and high heat generation conditions are solved, achieving a balance between high performance and green sustainability.

CN121159956APending Publication Date: 2025-12-19SICHUAN KALEVEI TECH CO LTD

Patent Information

Application Number
CN202511477156.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Existing tire transition layer compounds exhibit weak interfacial bonding under high stress and high heat generation conditions, leading to interfacial debonding, reduced compound fatigue life, poor dispersion of recycled carbon black, unsustainable material system, high environmental impact, and difficulty in achieving a balance between high performance and green sustainability.

Method used

By employing bio-based surface grafting technology to introduce carboxyl functional groups onto the surface of recycled carbon black, an ionic cross-linking network is formed through highly active zinc oxide, and a covalent cross-linking network is formed by combining bio-based adhesive resin and rubber. A multi-level pore structure is used to improve dispersibility, and bio-based materials are used to replace petroleum-based raw materials, thus achieving green and sustainable production.

Benefits of technology

It significantly improves the bonding strength, tensile and tear properties, weather resistance and heat resistance of the transition layer compound, achieving a balance between high performance and low environmental impact, realizing the high-value utilization of recycled carbon black and the sustainability of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a green and environment-friendly transition layer rubber material for a tire and a production process of the green and environment-friendly transition layer rubber material. The green and environment-friendly transition layer rubber material comprises the following raw materials: natural rubber, high-activity zinc oxide, a bio-based anti-aging agent RD, modified carbon black, N326 carbon black, bio-based bonding resin, sulfur and other auxiliaries. The production process comprises the following steps: 1) preparing modified carbon black; and 2) a third-stage internal mixing process. According to the invention, high-performance modified carbon black is firstly produced from waste tires, and then the high-performance modified carbon black is used as a part of filler to prepare the green and environment-friendly transition layer rubber material for tires; therefore, the scientific problems of poor reinforcing property and weak interface bonding of the recovered carbon black are solved, meanwhile, the quality of the filler is ensured through a multi-stage purification and activation process, finally, the performance breakthrough is realized on the molecular interface level, a green, circulating and sustainable production mode is realized on the process level, and the production cost is reduced. Therefore, the remarkable beneficial effects of high performance, high adhesion, high durability and low environmental load are comprehensively achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of transition layer rubber manufacturing, and particularly relates to a green and environment-friendly transition layer rubber for tires and a production process thereof. BACKGROUND

[0002] The tire manufacturing industry is a resource and energy intensive industry, and a large amount of non-renewable petroleum-based materials such as carbon black, various petroleum-based additives and synthetic rubber are relied on in the production process. At the same time, a large amount of waste tires are generated globally every year, and the treatment and recycling thereof has always been a serious environmental challenge. The traditional treatment methods such as landfill or incineration not only cause resource waste, but also bring about environmental problems such as soil pollution and air pollution. Therefore, developing green and sustainable high-performance tire materials and realizing high-value cyclic utilization of waste tires have become an inevitable trend of the industry.

[0003] The transition layer rubber is a key component in radial tires, which is located between the carcass ply and the tread rubber, and its core function is to transfer stress, buffer strain and ensure the durable and firm adhesion between the tread rubber and the carcass ply. Therefore, the transition layer rubber must have excellent mechanical properties, outstanding adhesion properties and durability such as fatigue resistance and heat aging resistance.

[0004] At present, the transition layer rubber in the tire industry at home and abroad generally has the following technical bottlenecks: First, the weak interface bonding restricts the upper limit of material performance. The existing technology widely uses conventional carbon black (such as N326, N330, etc.) as the main reinforcing filler. The interaction between carbon black and rubber molecular chains mainly depends on physical adsorption and limited physical-chemical action, and the interface bonding energy is low. This weak interface bonding is easy to fail under harsh conditions such as high stress and high heat, which leads to interface debonding and becomes the starting point of fatigue crack initiation, eventually causing the dynamic fatigue performance of the rubber to decrease and the adhesion performance to decay prematurely, affecting the overall life and reliability of the tire.

[0005] Second, the performance defects of recycled carbon black and the difficulty of high-value utilization. In order to solve the problem of black pollution, waste tire pyrolysis technology as a resource recycling method has been widely applied. However, the recycled carbon black (rCB) produced thereby contains a large amount of ash (such as ZnO, CaCO3, etc.), residual hydrocarbons and sulfides on the surface, and its surface energy is high and easy to agglomerate, which leads to poor dispersibility in the rubber matrix. If used in large quantities directly, a large amount of defects will be introduced, which will seriously deteriorate the mechanical properties and durability of the rubber. Therefore, recycled carbon black can only be used as a low-value filler in non-critical rubber products, and its application in high-performance tire transition layer rubber has always been difficult to break through, and it cannot realize real closed-loop high-value utilization.

[0006] Third, the material system is not sustainable and has high environmental load. The entire rubber compound formulation system relies heavily on petroleum-based raw materials, including newly produced carbon black, petroleum-based antioxidants (such as TMQ, 6PPD), petroleum-based adhesive resins (such as resorcinol-formaldehyde adhesives), etc. The production process of these materials has high energy consumption and large carbon emissions. In addition, traditional carbon black surface modification methods mostly use strong inorganic acids (such as nitric acid, sulfuric acid) or petroleum-based chemicals, which have environmental pollution risks and are contrary to the concept of green manufacturing.

[0007] In summary, the prior art cannot effectively balance high performance, high adhesion, high durability, and green sustainability. Either environmental protection is sacrificed for performance, or performance is compromised for environmental protection. Therefore, the industry urgently needs an innovative technical solution that can fundamentally strengthen the filler-rubber interfacial interaction, completely solve the dispersion and compatibility problems of recycled carbon black, and significantly increase the biobased content and sustainability of the material system, thereby manufacturing a new generation of environmentally friendly transition layer rubber compound with excellent comprehensive performance. SUMMARY

[0008] The purpose of the present application is to solve the problems existing in the prior art and provide a green and environmentally friendly tire transition layer rubber compound and its production process.

[0009] To achieve the above-mentioned purpose, the present application adopts the following technical solutions: The present application first proposes a production process for a green and environmentally friendly tire transition layer rubber compound, comprising the following steps: 1) First-stage mixing The natural rubber is wrapped around the roll and fed into the mixing chamber, high-activity zinc oxide, biobased antioxidant RD, modified carbon black, and 3 / 5 of N326 carbon black are added. The upper plunger is pressed down to start mixing. When the rubber temperature reaches 160±5℃, the rubber is immediately discharged to the sheeting machine, cooled after slicing, and the first-stage masterbatch is obtained. The rubber macromolecular chain is fully broken and plasticized under high temperature and high shear, and the modified carbon black, N326 filler, zinc oxide, and antioxidant are uniformly dispersed and preliminarily combined. 2) Second-stage mixing The first-stage masterbatch is fed into the mixing chamber, and biobased adhesive resin and the remaining N326 carbon black are added. The upper plunger is pressed down to continue mixing to ensure that the resin is completely melted and uniformly dispersed. When the rubber temperature reaches 160±5℃, the rubber is immediately discharged to the sheeting machine, cooled after slicing, and the second-stage masterbatch is obtained. The biobased adhesive resin is sensitive to temperature and can uniformly coat the fillers and rubber molecules after complete melting, preparing for the adhesion reaction during subsequent vulcanization. 3) Third-stage final mixing After the second-stage masterbatch is put into the internal mixer, low-temperature cooling water is immediately turned on to cool and stir the rubber compound at a low speed of 20-25 rpm to reduce the temperature of the rubber compound to below 80°C; the upper plunger is lifted, and sulfur and other additives are quickly added; the upper plunger is pressed down, and the rubber compound is mixed at a low speed for 45-60 s, and then the temperature of the rubber compound is raised to 100±5°C, and the rubber compound is immediately discharged; the final rubber compound is discharged to an open mill for further thinning, heat dissipation, extrusion, sheeting, cooling, and storage for at least 24 h to obtain a tire transition layer rubber compound.

[0010] Sulfur (S) and other vulcanization system components such as accelerators are added at a low temperature to prevent the rubber compound from being prematurely vulcanized (scorching) during the mixing stage. The low-speed short-time mixing only pursues uniform dispersion and does not pursue high temperature.

[0011] The high-activity zinc oxide reacts with the carboxyl groups (-COOH) of the itaconic acid grafted chains on the surface of the modified carbon black to form zinc itaconate, which forms a strong "ionic crosslinking" network in the rubber compound. This bonding force is much stronger than the ordinary van der Waals force, greatly enhancing the modulus and adhesion strength of the rubber compound; the bio-based adhesive resin reacts with the rubber hydrocarbon to form a covalent crosslinking network of resin-rubber during the vulcanization stage under the catalysis of zinc oxide and zinc stearate; at the same time, the polar groups such as the hydroxyl groups of the resin can also strongly interact with the functional groups on the surface of the modified carbon black, acting as a "bridge" to connect the filler on one end and the rubber molecules on the other end, significantly improving the interfacial adhesion.

[0012] Preferably, the preparation process of the modified carbon black comprises the following steps: S1, raw material pretreatment The waste tires are conveyed to the magnetic separator by the feeding machine to ensure uniform feeding; the drum speed of the magnetic separator is set to 30 rpm to adsorb the steel wires in the tires, and the rubber material enters the crushing process; the rubber is crushed to 5-10 mm by a double-shaft shredder, and then graded by a vibrating screen, and the 2-5 mm rubber powder enters the deoiling process, and the >5 mm rubber returns to the previous process for re-crushing, and the <2 mm rubber is used as a byproduct; the 2-5 mm rubber powder is sent to a vacuum deoiling machine to remove surface oil at 120-150°C under nitrogen protection to prevent oxidation, and the moisture content of the deoiled rubber powder is ≤2%, obtaining pretreated rubber powder; S2, two-stage temperature-controlled pyrolysis The pretreated rubber powder is heated and decomposed under anoxic conditions, and the long chains of polymers such as natural rubber (NR), styrene-butadiene rubber (SBR), and cis-butadiene rubber (BR) in the tires are broken to generate small-molecule volatile components (oil and gas) and solid carbon black; The pretreated rubber powder is fed into a rotary kiln, and the reaction is carried out at 420-450°C for 30-40 min, and the nitrogen flow is 50 NL / min to carry the volatile components, pyrolysis oil, and pyrolysis gas into a gas-liquid separator to obtain primary carbon black, and the primary carbon black falls into a fixed bed; Mainly complete the main pyrolysis stage of rubber polymer, and generate "primary carbon black". At this temperature, the carbon black yield is high, but the surface is covered with a large amount of heavy tar and hydrocarbon substances, and the structure is not pure.

[0013] 500-550℃ under the air, 15-20min, the residual volatile matter is removed, and the deep carbon black is obtained. The deep carbon black is sent into the activation unit by the screw conveyor; This is a controllable oxidation process. The trace oxygen from the air is introduced and reacts with the residual volatile matter and amorphous carbon to be oxidized into CO and CO2 gas and removed.

[0014] The refined carbon black removes the surface impurities, improves the purity, specific surface area and activity of the carbon black, and obtains "deep carbon black".

[0015] The gas-liquid separator condenses the pyrolysis oil and pyrolysis gas at 40℃, and after removing H2S by the purification tower, 80% is used for heating in the thermal activation unit, and 20% is externally supplied as boiler fuel; S3, bio-based surface grafting S3.1, bio-based demineralization The deep carbon black and the demineralizing agent are sent into the ultrasonic reactor, and ultrasonic reaction is carried out at 60-70℃ for 2h to remove impurities such as ZnO and CaCO3. After the reaction, the mixture enters the water washing machine, and countercurrent water washing is carried out until pH=6-7. The waste water is sent into the lignin adsorption tower. The water-washed carbon black is vacuum dried to obtain demineralized carbon black which is sent to the thermal activation section; Itaconic acid has two carboxyl groups and can react with metal oxides and carbonates; ; ;

[0016] Hydrofluoric acid is the only common acid that can effectively dissolve silicon dioxide;

[0017] The ultrasonic technology provides strong mechanical energy and cavitation effect, which can violently flush the carbon black aggregates, force the acid liquid into the internal pores of the aggregates, fully contact and react with the inorganic impurities wrapped therein, and greatly improve the demineralization efficiency and thoroughness. Countercurrent water washing removes the reaction products and residual acid.

[0018] S3.2, biochar cooperates with thermal activation The demineralized carbon black and the biochar are uniformly mixed by a mixer, sent into a tubular furnace, and activated at 750-800℃ under nitrogen protection for 60min. The biochar releases CO2 / H2O to etch the carbon black to form multi-level pores. After activation, the mixture is separated by air flow, the biochar returns to the mixer for recycling, and the activated carbon black enters the surface grafting section; The CO2 and H2O produced by the decomposition of biochar at high temperature act as mild gasification agents to selectively "etch" the amorphous carbon regions with more structural defects and higher reactivity in the reclaimed carbon black. This process creates new micropores and mesopores on the carbon black particles, forming a hierarchical pore structure. This structure can provide stronger physical anchoring and greater specific surface area for interaction with rubber molecular chains when used as a rubber filler, thereby enhancing the reinforcing effect. Nitrogen protection prevents the oxidation of carbon black by air.

[0019] S3.3, Bio-based surface grafting The activated carbon black, bio-based itaconic acid, and ammonium persulfate are fed into a reaction kettle, and the reaction is stirred at 80-90°C for 1.5h. The itaconic acid is grafted onto the surface of the carbon black by free radical addition. The reaction liquid is centrifuged, and the solid phase is the grafted carbon black. The liquid phase is recovered and purified for reuse. The grafted carbon black is dried by hot air to obtain modified carbon black. Ammonium persulfate ((NH4)2S2O8) decomposes to produce sulfate anion radicals (SO4 - •) under heating. SO4 - • attacks the bio-based itaconic acid molecules, making them free radical active monomers. There are a large number of active sites on the surface of carbon black, such as unsaturated carbon at the edge and functional groups. The itaconic acid radicals combine with these sites, and grafting copolymerization occurs, forming polymer chains or grafting polar functional groups such as carboxyl (-COOH) and olefin (-C=CH2) on the surface of carbon black. The grafted polar molecular chains can effectively isolate the carbon black particles during mixing, reducing their tendency to agglomerate due to van der Waals forces, and making them more uniformly dispersed in rubber. The introduced functional groups such as carboxyl (-COOH) can physically entangle with the molecular chains of natural rubber. More importantly, they can chemically react with zinc oxide (ZnO) and bio-based adhesive resin in the compound, forming strong ionic or coordination bonds, greatly enhancing the interfacial adhesion strength of the filler and rubber.

[0020] S4, post-treatment The wastewater produced during the process, including water washing wastewater and centrifugal mother liquor, and the exhaust gas, including pyrolysis tail gas and drying tail gas, are purified and treated.

[0021] Preferably, in S1, the waste tires include 70% passenger car tires and 30% light truck tires; the initial water content of the tires is ≤8%, and the steel content is ≤1.5wt%.

[0022] Preferably, in 3.1, the demineralizing agent is a 15% bio-based itaconic acid aqueous solution and hydrofluoric acid, and the volume ratio of the bio-based itaconic acid aqueous solution to hydrofluoric acid is 9:1; the mass ratio of the deep carbon black to the demineralizing agent is 1:8.

[0023] Preferably, in 3.2, the biochar is rice husk biochar; the mass ratio of the demineralized carbon black to the biochar is 10:1.

[0024] Preferably, in 3.3, the mass ratio of the activated carbon black, the aqueous solution of bio-based itaconic acid, and the aqueous solution of ammonium persulfate is 2:25:1; the mass fraction of the aqueous solution of bio-based itaconic acid is 5-8%, and the mass fraction of the aqueous solution of ammonium persulfate is 2%.

[0025] Preferably, the mass ratio of the natural rubber, the high-activity zinc oxide, the bio-based antioxidant RD, the modified carbon black, the N326 carbon black, the bio-based adhesive resin, and the sulfur is 100:5:2:10-20:30-40:3:2.5. The content of zinc oxide in the high-activity zinc oxide is about 85%. The bio-based adhesive resin specifically refers to a resorcinol-itaconic acid-formaldehyde resin. Other auxiliary agents include a sulfenamide vulcanization accelerator, the amount of which is 0.8-1.5% of the mass of the natural rubber; a stearic acid active agent, the amount of which is 0.2-0.5% of the mass of the natural rubber; an N-cyclohexyl thio-phthalimide scorch retarder, the amount of which is 0.1-0.3% of the mass of the natural rubber; a bio-based oil plasticizer, the amount of which is 2-4% of the mass of the natural rubber; and a polymer dispersant, the amount of which is 2-3% of the mass of the natural rubber.

[0026] The present application also provides a green and environmentally friendly tire transition layer material prepared by the above production process, which has high adhesion strength, excellent tensile and tear properties, weather resistance, and heat resistance, and meets the long-term use requirements of the tire.

[0027] Compared with the prior art, the present application has the following beneficial effects: 1. The conventional transition layer material uses conventional carbon black, such as N326, and the combination of carbon black and rubber molecules mainly depends on physical action and limited physical-chemical adsorption, and the interface bonding force is relatively weak, which is prone to interface debonding under harsh conditions such as high stress and heat generation, resulting in a decrease in the fatigue life of the material and a decrease in the adhesion performance.

[0028] In the present application, carboxyl functional groups (-COOH) of itaconic acid are introduced on the surface of the recycled carbon black by bio-based surface grafting technology, and these functional groups chemically react with high-activity zinc oxide (ZnO) in the material during mixing and vulcanization to generate a strong zinc itaconate salt.

[0029]

[0030] This process builds a strong crosslinking network composed of ionic bonds at the filler-rubber interface. The bond energy of ionic bonds is much higher than that of traditional van der Waals forces, thus realizing high adhesion strength, excellent tensile and tear properties; ionic bonds provide extremely firm interface bonding, making the adhesion of the transition layer compound to other components such as the carcass cord more durable and reliable, and the strong interface ensures that stress can be effectively transmitted from the relatively soft rubber matrix to the rigid carbon black filler, so that the filler can fully play a reinforcing role, and the macroscopic performance is a significant improvement in modulus, tensile strength and tear strength.

[0031] 2. In the prior art, the surface of recycled carbon black is extremely easy to form stable aggregates due to residual impurities and its high surface energy, and it is difficult to disperse uniformly in rubber. Poor dispersion can lead to stress concentration points, which become the starting point of crack initiation, seriously damaging the mechanical properties and durability of the compound.

[0032] The present application solves the dispersion problem through a three-step method of "de-mineralization + activation + grafting". Specifically, de-mineralization removes inorganic salts (ZnO, CaCO3) wrapped in carbon black aggregates, which is beneficial to subsequent dispersion; gasification etching creates multi-level pores on the surface of carbon black, not only increasing the specific surface area, but also making it easier for rubber molecular chains to penetrate and anchor; the grafted itaconic acid molecular chains enhance the steric hindrance effect during mixing, effectively isolating the particles and preventing their re-aggregation. The modified carbon black can be uniformly dispersed in rubber as primary aggregates, greatly reducing performance defects caused by uneven dispersion, making the compound performance more uniform and stable.

[0033] 3. Traditional technology relies heavily on petroleum-based raw materials, such as new carbon black, petroleum-based antioxidants, and petroleum-based resins, with high energy consumption and large carbon emissions in the production process; the disposal of waste tires is mostly incineration or landfill, causing resource waste and environmental pollution.

[0034] The present application converts waste tires into primary carbon black through pyrolysis, realizing closed-loop utilization of resources, and replacing traditional mineral acid and petroleum-based modifiers with bio-based itaconic acid; replacing petroleum-based antioxidants RD and bio-based adhesion resins with bio-based antioxidants RD and bio-based adhesion resins; these bio-based materials have renewable properties, reducing the carbon footprint throughout the life cycle; the oil gas produced by pyrolysis is purified and used as fuel for the activation unit, significantly reducing external energy consumption. Biochar can be recycled after activation, reducing material consumption.

[0035] In summary, the present application solves the scientific problems of poor reinforcing performance and weak interface bonding of recycled carbon black by the innovative concept of bio-based chemical grafting and ionic bond crosslinking, and ensures the quality of the filler through a multi-stage purification and activation process, ultimately achieving performance breakthroughs at the molecular interface level and a green, circular, and sustainable production mode at the process level, thereby comprehensively bringing about the significant beneficial effects of high performance, high adhesion, high durability, and low environmental load. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments, comparative examples, and corresponding charts of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments.

[0037] The purity and manufacturers of each drug used in the experiment are shown in Table 1: Table 1. Raw drug information

[0038] Preparation Example 1: S1, raw material pretreatment The waste tire is conveyed to the magnetic separator by the feeding machine to ensure uniform feeding. The magnetic separator drum speed is set to 30 rpm to adsorb the steel wire in the tire, and the rubber material enters the crushing process. The rubber is crushed to 5-10 mm by a double-shaft shredder, and then graded by a vibrating screen. The 2-5 mm rubber powder enters the deoiling process, and the >5 mm rubber returns to the previous process for re-crushing. The <2 mm rubber is used as a byproduct. The 2-5 mm rubber powder is sent to a vacuum deoiling machine to remove surface oil at 120-150°C under nitrogen protection to prevent oxidation. The moisture content of the deoiled rubber powder is ≤2%, and the pretreated rubber powder is obtained. S2, two-stage temperature-controlled pyrolysis The pretreated rubber powder is fed into a rotary kiln and reacted at 420-450°C for 35 min. Nitrogen gas with a flow rate of 50 NL / min carries the volatile matter, pyrolysis oil, and pyrolysis gas into a gas-liquid separator to obtain primary carbon black. The primary carbon black falls into a fixed bed. Air with a flow rate of 1.5 NL / min is introduced at 500-550°C to remove residual volatile matter within 15-20 min to obtain deep carbon black. The deep carbon black is sent to an activation unit by a screw conveyor. The gas-liquid separator condenses the pyrolysis oil and pyrolysis gas at 40°C. After removing H2S through a purification tower, 80% of the pyrolysis oil and pyrolysis gas are used for heating in the thermal activation unit, and 20% are externally supplied as boiler fuel. S3, bio-based surface grafting S3.1, bio-based demineralization Deep carbon black and demineralizing agent are fed into an ultrasonic reactor and ultrasonically reacted at 60-70℃ for 2 hours to remove impurities such as ZnO and CaCO3. After the reaction, the mixture enters a water washing machine and is washed countercurrently until the pH reaches 6-7. The wastewater is then sent to a lignin adsorption tower. The washed carbon black is vacuum dried to obtain demineralized carbon black, which is then transported to the thermal activation section. S3.2, Biochar Synergistic Thermal Activation Demineralized carbon black and biochar are uniformly mixed in a mixer and fed into a tube furnace. They are activated at 750-800℃ under nitrogen protection for 60 minutes. The biochar releases CO2 / H2O to etch the carbon black and form multi-level channels. After activation, the mixture is separated by airflow. The biochar is returned to the mixer for circulation, and the activated carbon black enters the surface grafting section. S3.3, Bio-based surface grafting Activated carbon black, bio-based itaconic acid, and ammonium persulfate were fed into a reactor and stirred at 80-90℃ for 1.5 h. Itaconic acid was grafted onto the carbon black surface via free radical addition. The reaction solution was separated by centrifugation, and the solid phase was the grafted carbon black. The liquid phase was recovered, purified, and reused. The grafted carbon black was dried with hot air to obtain modified carbon black. S4, Post-processing Wastewater from the production process, including washing wastewater and centrifugal mother liquor, and exhaust gas, including pyrolysis tail gas and drying tail gas, are purified.

[0039] In S1, the waste tires include 70% passenger car tires and 30% light truck tires; the initial moisture content of the tires is ≤8% and the steel content is ≤1.5wt%.

[0040] In section 3.1, the demineralizing agent is a 15% (w / w) aqueous solution of bio-based itaconic acid and hydrofluoric acid, wherein the volume ratio of the aqueous solution of bio-based itaconic acid and hydrofluoric acid is 9:1; and the mass ratio of deep carbon black to the demineralizing agent is 1:8.

[0041] In section 3.2, the biochar is rice husk biochar; the mass ratio of demineralized carbon black to biochar is 10:1.

[0042] In section 3.3, the mass ratio of activated carbon black, bio-based itaconic acid aqueous solution, and ammonium persulfate aqueous solution is 2:25:1; wherein the mass fraction of the bio-based itaconic acid aqueous solution is 5-8%, and the mass fraction of the ammonium persulfate aqueous solution is 2%.

[0043] Example 1: 1) A period of secret practice Natural rubber is rolled into a mixing chamber, and high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, and 3 / 5 of N326 carbon black are added. The top bolt is pressed down to start mixing. When the rubber compound temperature reaches 160±5℃, it is immediately discharged to the sheeting machine. After being sliced ​​and cooled, a section of masterbatch is obtained. 2) Second stage of secret refining Put a section of masterbatch into the mixing chamber, and add bio-based adhesive resin and the remaining N326 carbon black; press down the upper ram to continue mixing, ensure that the resin is completely melted and uniformly dispersed; when the temperature of the rubber reaches 160±5℃, immediately discharge the rubber to the sheeting machine, after slicing, cool down, and get the second section of masterbatch; 3) Three-stage final refining After the second section of masterbatch is put into the mixer, immediately turn on the low-temperature cooling water, and cool and stir the rubber at a low speed of 20-25 rpm to reduce the temperature of the rubber to below 80℃; lift the upper ram, and quickly add sulfur and other additives; press down the upper ram, mix at a low speed for 45-60s, and raise the temperature of the rubber to 100±5℃, then immediately discharge the rubber; discharge the final refined rubber to the open mill for further thinning, heat dissipation, and extrusion and sheeting, cool down, and store for at least 24h to obtain the tire transition layer rubber.

[0044] The mass ratio of the natural rubber, high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, N326 carbon black, bio-based adhesive resin, and sulfur is 100:5:2:10:40:3:2.5; The content of zinc oxide in the high-activity zinc oxide is about 85%; The bio-based adhesive resin specifically refers to resorcinol-itaconic acid-formaldehyde resin; The other additives include sulfenamide vulcanization accelerator, with a dosage of 0.8% of the mass of the natural rubber; stearic acid activator, with a dosage of 0.5% of the mass of the natural rubber; N-cyclohexyl thio phthalimide anti-scorching agent, with a dosage of 0.1% of the mass of the natural rubber; bio-based oil plasticizer, with a dosage of 4% of the mass of the natural rubber; and polymer dispersant, with a dosage of 2% of the mass of the natural rubber.

[0045] Example 2: Prepare the green and environmentally friendly tire transition layer rubber according to the preparation method of Example 1, but the mass ratio of the natural rubber, high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, N326 carbon black, bio-based adhesive resin, and sulfur is 100:5:2:15:35:3:2.5; The content of zinc oxide in the high-activity zinc oxide is about 85%; The bio-based adhesive resin specifically refers to resorcinol-itaconic acid-formaldehyde resin; The other additives include sulfenamide vulcanization accelerator, with a dosage of 1.15% of the mass of the natural rubber; stearic acid activator, with a dosage of 0.35% of the mass of the natural rubber; N-cyclohexyl thio phthalimide anti-scorching agent, with a dosage of 0.2% of the mass of the natural rubber; bio-based oil plasticizer, with a dosage of 3% of the mass of the natural rubber; and polymer dispersant, with a dosage of 2.5% of the mass of the natural rubber.

[0046] Example 3: A green transition layer for green tires was prepared according to the preparation method of Example 1, but the mass ratio of the natural rubber, high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, N326 carbon black, bio-based adhesive resin, and sulfur was 100:5:2:20:30:3:2.5. The content of zinc oxide in the high-activity zinc oxide was about 85%. The bio-based adhesive resin specifically refers to a resorcinol-itaconic acid-formaldehyde resin. Other additives include a sulfenamide vulcanization accelerator, the amount of which was 1.5% of the mass of the natural rubber; a stearic acid activator, the amount of which was 0.2% of the mass of the natural rubber; an N-cyclohexyl thio phthalimide anti-scorching agent, the amount of which was 0.3% of the mass of the natural rubber; a bio-based oil plasticizer, the amount of which was 2% of the mass of the natural rubber; and a polymer dispersant, the amount of which was 3% of the mass of the natural rubber.

[0047] Accordingly, the following were also designed: Comparative Example 1: The same as the formulation and experimental method of Example 2, but a petroleum-based antioxidant was used instead of the bio-based antioxidant RD; Comparative Example 2: The same as the formulation and experimental method of Example 2, but a petroleum-based resin was used instead of the bio-based adhesive resin; Comparative Example 3: The same as the formulation and experimental method of Example 2, but only new carbon black was used instead of the modified carbon black; Comparative Example 4: The same as the formulation and experimental method of Example 2, but the mass ratio of the natural rubber, high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, N326 carbon black, bio-based adhesive resin, and sulfur was 100:5:2:5:45:3:2.5. Comparative Example 5: The same as the formulation and experimental method of Example 2, but the mass ratio of the natural rubber, high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, N326 carbon black, bio-based adhesive resin, and sulfur was 100:5:2:35:15:3:2.5. According to the standards and test methods of GB / T 1232.1 “Unvulcanized rubber-Determination of viscosity using a disc-type viscometer-Part 1: Determination of Mooney viscosity”, GB / T 528 “Vulcanized or thermoplastic rubber-Determination of tensile stress-strain properties”, GB / T 3513 “Vulcanized rubber-Determination of shear tensile strength of adhesion to metal”, GB / T 7760 “Vulcanized or thermoplastic rubber-Determination of adhesion strength to rigid board-90° peel method”, GB / T 3512 “Vulcanized or thermoplastic rubber-Hot air accelerated aging and heat resistance test”, GB / T 13934 “Vulcanized or thermoplastic rubber-Determination of flex cracking and crack growth (Dynamometer type)”, the present application is detected in terms of the curing time (t90), scorch time, tensile properties, adhesion properties to steel cord, adhesion properties to organic cord and to tread rubber, hot air aging properties, fatigue properties, etc., and the corresponding results and data are summarized and plotted in Table 2: Table 2. Performance detection data of the transition layer rubber compound for green and environmentally friendly tires

[0048] Data analysis: From the comparison of Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, it can be seen that: The comparison between Comparative Example 1 and Example 2 mainly reflects the influence of the migration and persistence of the antioxidant molecules on the aging properties. The antioxidant delays the aging process by capturing free radicals and decomposing hydrogen peroxide generated during the aging process of the rubber. Many petroleum-based antioxidants have small molecular weights or low polarity, and are prone to migrate, volatilize or seep to the surface from the interior of the rubber during long-term heat aging, resulting in rapid decay of the protective effect. The bio-based antioxidant RD used has a higher molecular weight and a larger molecular structure, and is not prone to migration and volatilization. The bio-based molecular structure contains multiple active groups, providing multiple protection mechanisms. In Comparative Example 1, the petroleum-based antioxidant is effective in the early stage of aging, but is quickly consumed or lost as time goes on, resulting in severe damage to the rubber network, chain segment breakage and abnormal increase in crosslinking density. The bio-based antioxidant RD provides more persistent and stable protection, allowing the rubber network to maintain good integrity and elasticity after aging.

[0049] Comparative Example 2 vs. Example 2 reveals the decisive influence of the chemical structure of the adhesive resin on the interfacial adhesion, traditional petroleum-based adhesive resins mainly rely on phenolic hydroxyl and methylene bridge to play a role. While the bio-based resorcinol-itaconic acid-formaldehyde resin used in the example introduces the key itaconic acid unit, bringing a large number of carboxyl groups (-COOH), the role of the adhesive resin is to act as a "molecular bridge" between the hydrophobic rubber and the hydrophilic cord surface, the carboxyl groups on the bio-based resin form stronger chemical bonds or ionic bonds with the zinc layer of the steel wire or the polar groups of the organic cord, such as zinc soap bonds; combined with the carboxyl groups on the surface of the modified carbon black through hydrogen bonds or ionic interactions to form covalent bonds; the reactive groups of the resin can co-crosslink with the rubber molecular chain during the vulcanization process, anchoring it in the rubber network; the itaconic acid unit in the bio-based adhesive resin provides high-activity carboxyl groups, achieving stronger and more durable chemical bonding between the cord, filler and rubber, thereby significantly improving the adhesion performance.

[0050] Comparative Example 3 vs. Example 2 demonstrates the importance of filler-rubber interfacial interaction, Comparative Example 3 is significantly inferior to Example 2 in terms of tensile strength, adhesion performance and fatigue resistance; ordinary carbon black, such as N660, has a certain activity on the surface, but mainly physical adsorption and limited chemical bonding, while modified carbon black has undergone bio-based itaconic acid surface grafting, introducing a large number of carboxyl groups (-COOH) and other polar functional groups on the surface, these polar groups can produce stronger interactions with the rubber molecular chain, especially the polar components such as proteins in natural rubber, forming a more secure "bound rubber" layer, greatly improving stress transfer efficiency, directly manifested as higher tensile strength and modulus; when combined with the cord, the carboxyl groups easily form chemical bonding or strong polar adsorption with the oxide layer on the surface of the metal cord or the active groups of the organic cord, thus the H pull-out force and peel strength are greatly improved; the modified carbon black has undergone biochar synergistic thermal activation, forming a rich multi-level pore structure, which not only increases the specific surface area, enhancing the physical interlocking effect with the rubber, but also provides space for the embedding of the rubber molecular chain, making the filler network more stable, while ordinary carbon black has a relatively dense structure, lacking this effect; the itaconic acid layer grafted on the surface improves the compatibility and dispersion of the carbon black in the rubber matrix, uniformly dispersed fillers can more effectively share the load and avoid stress concentration, while the use of ordinary carbon black in Comparative Example 3 is more prone to agglomeration, forming weak points, leading to a sharp decline in fatigue resistance (crack growth rating D), agglomerates are also stress concentration points, easily causing cracking; the modified carbon black builds a stronger and more stable filler-rubber-cord composite interface through enhanced chemical bonding / polar interaction, optimized physical interlocking and excellent dispersion.

[0051] From the comparison of Example 2, Comparative Example 5, Comparative Example 4, it can be seen that the performance of the rubber compound is largely determined by the network structure formed by the filler. If the amount of filler is too low, the network is weak and the reinforcement is insufficient; if the amount of filler is too high, the network is too dense and rigid, and defects are prone to occur; One of the core functions of the transition layer rubber compound is adhesion. The adhesion performance of Comparative Example 4 is the worst, because it mainly relies on N326 carbon black, which has inert surface and cannot form effective chemical bonding with the metal plating layer or the polar cord. Adhesion mainly relies on the adhesion of the rubber itself, and the strength is limited; the adhesion performance of Comparative Example 5 and Example 2 is excellent. The carboxyl groups on the surface of the modified carbon black can form coordination bonds or ionic bonds with the copper / zinc plating layer of the steel wire, and can produce strong hydrogen bonds or chemical bonds with the polar groups in the bio-based adhesive resin (resorcinol-itaconic acid-formaldehyde resin), thereby bridging to the cord through the resin. Although the adhesion of Comparative Example 5 is slightly higher, the brittle matrix makes it perform worse in dynamic fatigue test than Example 2.

[0052] The above description is only the preferred specific embodiments of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art can make equivalent replacements or changes to the technical solutions and the inventive concept of the present application within the technical scope disclosed by the present application, which should be covered within the protection scope of the present application.

Claims

1. A production process for a green and environmentally friendly transition layer rubber compound for tires, characterized in that, Includes the following steps: 1) A period of secret practice Natural rubber is rolled into a mixing chamber, and high-activity zinc oxide, bio-based antioxidant RD, modified carbon black, and 3 / 5 of N326 carbon black are added. The top bolt is pressed down to start mixing. When the rubber compound temperature reaches 160±5℃, it is immediately discharged to the sheeting machine. After being sliced ​​and cooled, a section of masterbatch is obtained. 2) Second stage of secret refining A first stage of masterbatch is put into the mixing chamber, along with bio-based adhesive resin and the remaining N326 carbon black; the top plug is pressed down to continue mixing, ensuring that the resin is completely melted and evenly dispersed; when the temperature of the rubber compound reaches 160±5℃, it is immediately discharged to the sheeting machine, and after being sliced ​​and cooled, a second stage of masterbatch is obtained. 3) The final stage of the three-stage training After the second-stage masterbatch is fed into the internal mixer, the low-temperature cooling water is immediately turned on, and the rubber compound is cooled and stirred at a low speed of 20-25 rpm to reduce the temperature of the rubber compound to below 80℃. The top plug is raised, and sulfur and other additives are quickly added. The top plug is pressed down, and the mixture is mixed at a low speed for 45-60 seconds until the rubber compound rises to 100±5℃. The rubber compound is then discharged immediately. The final compound is discharged to the open mill for further heat dissipation, extrusion and sheeting, cooling, and left to stand for at least 24 hours to obtain the transition layer rubber compound for tires.

2. The production process of a green and environmentally friendly transition layer rubber compound for tires according to claim 1, characterized in that, The preparation process of the modified carbon black includes the following steps: S1. Raw material pretreatment Waste tires are conveyed to a magnetic separator via a feeder to ensure uniform feeding. The magnetic separator drum speed is set to 30 rpm to adsorb the steel wires inside the tires, and the rubber material enters the crushing process. The rubber is crushed to 5-10 mm by a twin-shaft shredder, and then classified by a vibrating screen. Rubber powder of 2-5 mm enters the deoiling process, rubber >5 mm is returned to the previous process for re-crushing, and rubber <2 mm is kept as a by-product. The 2-5 mm rubber powder is sent to a vacuum deoiler to remove surface oil at 120-150℃, with nitrogen protection to prevent oxidation. After deoiling, the moisture content of the rubber powder is ≤2%, resulting in pretreated rubber powder. S2, Dual-stage temperature-controlled pyrolysis Pretreated rubber powder is fed into a rotary kiln and reacted at 420-450℃ for 30-40 minutes. Nitrogen gas at a flow rate of 50 NL / min carries volatiles, pyrolysis oil, and pyrolysis gas into a gas-liquid separator to obtain primary carbon black, which falls into a fixed bed. Air is then introduced at 500-550℃ at a flow rate of 1-2 NL / min to remove residual volatiles within 15-20 minutes, yielding deep carbon black. The deep carbon black is then conveyed to the activation unit via a screw conveyor. The gas-liquid separator condenses pyrolysis oil and pyrolysis gas at 40℃. After H2S is removed by the purification tower, 80% is used for heating the thermal activation unit and 20% is supplied externally as boiler fuel. S3, Bio-based surface grafting S3.1, Bio-based Demineralization Deep carbon black and demineralizing agent are fed into an ultrasonic reactor and ultrasonically reacted at 60-70℃ for 2 hours to remove impurities such as ZnO and CaCO3. After the reaction, the mixture enters a water washing machine and is washed countercurrently until the pH reaches 6-7. The wastewater is then sent to a lignin adsorption tower. The washed carbon black is vacuum dried to obtain demineralized carbon black, which is then transported to the thermal activation section. S3.2, Biochar Synergistic Thermal Activation Demineralized carbon black and biochar are uniformly mixed in a mixer and fed into a tube furnace. They are activated at 750-800℃ under nitrogen protection for 60 minutes. The biochar releases CO2 / H2O to etch the carbon black and form multi-level channels. After activation, the mixture is separated by airflow. The biochar is returned to the mixer for circulation, and the activated carbon black enters the surface grafting section. S3.3, Bio-based surface grafting Activated carbon black, bio-based itaconic acid, and ammonium persulfate were fed into a reactor and stirred at 80-90℃ for 1.5 h. Itaconic acid was grafted onto the carbon black surface via free radical addition. The reaction solution was separated by centrifugation, and the solid phase was the grafted carbon black. The liquid phase was recovered, purified, and reused. The grafted carbon black was dried with hot air to obtain modified carbon black. S4, Post-processing Wastewater from the production process, including washing wastewater and centrifugal mother liquor, and exhaust gas, including pyrolysis tail gas and drying tail gas, are purified.

3. The production process of a green and environmentally friendly transition layer rubber compound for tires according to claim 2, characterized in that, In S1, the waste tires include 70% passenger car tires and 30% light truck tires; the initial moisture content of the tires is ≤8% and the steel content is ≤1.5wt%.

4. The production process of a green and environmentally friendly transition layer rubber compound for tires according to claim 2, characterized in that, In section 3.1, the demineralizing agent is a 15% (w / w) aqueous solution of bio-based itaconic acid and hydrofluoric acid, wherein the volume ratio of the aqueous solution of bio-based itaconic acid and hydrofluoric acid is 9:1; and the mass ratio of deep carbon black to the demineralizing agent is 1:

8.

5. The production process of a green and environmentally friendly transition layer rubber compound for tires according to claim 2, characterized in that, In section 3.2, the biochar is rice husk biochar; the mass ratio of demineralized carbon black to biochar is 10:

1.

6. The production process of a green and environmentally friendly transition layer rubber compound for tires according to claim 2, characterized in that, In section 3.3, the mass ratio of activated carbon black, bio-based itaconic acid aqueous solution, and ammonium persulfate aqueous solution is 2:25:1; wherein the mass fraction of the bio-based itaconic acid aqueous solution is 5-8%, and the mass fraction of the ammonium persulfate aqueous solution is 2%.

7. The production process of a green and environmentally friendly transition layer rubber compound for tires according to claim 1, characterized in that, The mass ratio of the natural rubber, highly active zinc oxide, bio-based antioxidant RD, modified carbon black, N326 carbon black, bio-based adhesive resin, and sulfur is 100:5:2:10-20:30-40:3:2.

5. The zinc oxide content in highly active zinc oxide is approximately 85%. Bio-based adhesive resins specifically refer to resorcinol-itaconic acid-formaldehyde resins; Other additives include sulfenamide vulcanization accelerators, used at 0.8-1.5% of the natural rubber mass; stearic acid activators, used at 0.2-0.5% of the natural rubber mass; N-cyclohexylthiophthalimide scorch inhibitors, used at 0.1-0.3% of the natural rubber mass; bio-based oil plasticizers, used at 2-4% of the natural rubber mass; and polymeric dispersants, used at 2-3% of the natural rubber mass.

8. A green and environmentally friendly transition layer rubber compound for tires prepared by the production process described in any one of claims 1-7, characterized in that, This tire transition layer compound has high adhesive strength, excellent tensile and tear properties, and is weather-resistant and heat- and oxygen-resistant, making it suitable for the long-term use requirements of tires.

Citation Information

Patent Citations

  • Preparation method of aqueous self-dispersing nanometer carbon black

    CN106634059A

  • Tire transition layer rubber as well as preparation method and application thereof

    CN118755155A

  • Pyrolysis carbon black reinforced tire transition layer rubber material and preparation method thereof

    CN119955184A

  • Waste tire pyrolysis carbon black upgrading and purifying method

    CN120290018A

  • Rubber composition for tire and tire

    JP2005002295A

Cited By

  • Automobile radial tire rubber material with excellent sound absorption performance, preparation method and tire

    CN121652479A